Application and verification of Next-Generation Sequencing (NGS) for the molecular diagnostics of brain tumours - Pinto, Maria de Azevedo (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017